Evaluation of the efficacy of various root canal irrigants on removal of smear layer in primary teeth: A comparative study - Adel S Alqarni; Muadh A AlGomaiah (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of the current research was to appraise the effectiveness of different radicular canal irrigant solutions on the elimination of the smear layer in deciduous teeth. Materials and Methods: A total of 60 fit deciduous teeth that were subjected to extraction for a variety of curative reasons were employed in this research. Every sample tooth was subjected to decoronation at the CEJ employing a carborundum disk. A number 10 K-file (Dentsply Maillefer) was utilized to estimate the working length of the radicular canal using a manual technique by a sole operator in the step-back method. The specimens were allocated at random to one of the following three groups: Group 1: Irrigation using Saline, Group 2: Irrigation using 6% Citric acid, and Group 3: Irrigation using sodium hypochlorite. Following 24 h of storage, the sample teeth were subjected to vertical grooving using diamond suctioning discs beneath a high-power suction. All sections were subjected to staining using 1% methylene blue for 2 min before rinsing with 0.9% saline and allowed to bench dry. Rendering scores for the existence of a smear layer for the two halves of the split sample tooth were performed by visual inspection for the cervical, middle, plus apical one-third via a light stereomicroscope at 40× magnifying power. Results: With saline irrigation, the smear coat elimination at coronal one-third scored at 2.16 ± 0.11, 1.84 ± 0.06 at middle one-third, along with 1.92 ± 0.26 at the apical one-third. When 6% citric acid was employed as an irrigant, the scores were 0.72 ± 0.14 at coronal one-third, 0.84 ± 0.03 at middle one-third, and 0.90 ± 0.23 at apical one-third. When sodium hypochlorite was used as an irrigant, the mean score was 0.78 ± 0.12 at the coronal one-third, 0.92 ± 0.06 at the middle one-third, as well as 0.96 ± 0.18 at the apical one-third. The differences between the groups were statistically significant. Conclusion: The current in-vitro research arrived at a conclusion that 6% citric acid has the potential to eliminate smear coats in deciduous radicular canals when employed as a closing irrigant following instrumentation.